Offenders in focus : risk, responsivity and diversity - Farrow, Kathryn; Kelly, Gill , 1967-; Wilkinson, Bernadette (Bristol, UK : Policy, 2007)
Drawing on research and integrating this with practitioner experience, this text creates research-based practice wisdom for engaging effectively with offenders
1. Context -- 2. Diversity-explores the issue of working with differences -- 3. Responsivity-examines the complexities of working with offenders who have other significant problems -- 4. Risk-tackles the issue of responding to offenders who illustrate different of risk -- 5. Conclusions
Includes bibliographical references and index
Keywords: Criminals -- Rehabilitation; Social work with criminals